Development and validation of a structured questionnaire for assessing risk factors of medication non-adherence among pulmonary tuberculosis patients in Indonesia - Rianto, Leonov; Agustina, Ika; Alfian, Sofa D.; Iskandarsyah, Aulia; Pradipta, Ivan Surya; Abdulah, Rizky (Frontiers in Pharmacology, 2024)
Background: Medication nonadherence is a significant concern in tuberculosis (TB) treatment, requiring a precise understanding of the associated risk factors. However, there is a lack of appropriate means to assess the risk factors among TB patients in Indonesia, leading to the development and validation of a structured questionnaire for this purpose.Method: This study unfolded in two distinct phases, namely, the first included questionnaire construction through framework development, item generation, item screening, and pretesting (in 50 patients). The second comprised questionnaire validation with 346 participants using confirmatory factor analysis (CFA) and structural equation modeling-partial least squares (SEM-PLS). Additionally, reliability testing was conducted using Cronbach's alpha and composite reliability statistical techniques.Results: In the development phase, 168 items were defined, consisting of sociodemographic characteristics (8 items) and risk factors for medication nonadherence (160 items). Expert evaluation reduced the number of items to 60, which decreased to 22 after performing a pilot study. Subsequent SEM-PLS modeling resulted in the identification of 14 valid items, representing five major risk factors, namely socioeconomics (4 items), health care team (4 items), condition (3 items), therapy (2 items), and patient (1 item). Only condition-related factors were found to influence nonadherence, and all constructs showed good reliability based on Cronbach's alpha (>0.6) and composite reliability (0.7) values.The final 22 items that emerged from this rigorous process indicated a valid and robust questionnaire for assessing risk factors of medication nonadherence among pulmonary tuberculosis patients in Indonesia.. The developed questionnaire was positioned to be a valuable tool for healthcare professionals, policymakers, and scientists in creating patient-centered strategies and interventions to address nonadherence.